Appendix 4.18: Ferdinand Marcos’s Self-Serving Presidential Decrees - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
To Marcos loyalists, Ferdinand Marcos should be remembered as a benevolent lawgiver, e.g., the president who declared the country a land reform area (but limited agrarian reform to rice and corn lands) and mandated employers to give thirteenth month pay to all of their employees (who earned up to PHP 1,000.00 a month, as per Presidential Decree No. 851, s. 1975). But a number of Marcos decrees can accurately be described as self-serving. Marcos is perhaps the only president to name a public institution after his father (converting the Ilocos Norte Institute of Technology into the Mariano Marcos Memorial College of Science and Technology) and, more egregiously, ratifying the illegal naming of one after himself. In the latter case, Marcos elevated Bayombong Hospital, a municipal-level institution, whose name had been changed to Major Ferdinand E. Marcos Hospital by the Municipal Council of Bayombong, into the Major Ferdinand E. Marcos Veterans Regional Hospital via presidential decree. Had Marcos not done so, the renaming could have been challenged as illegal based on Republic Act 1059 (see footnote 1 on page 20); Presidential Decree 306 implicitly amended Republic Act 1059. Thereafter, Marcos clarified via another presidential decree that the “regional” hospital was under the administrative supervision and control solely of the nationallevel Department of Health, making it a national hospital in all but name.